Quantitive Methods for Business Decisions / Fourth Edition - Curwin Jon; Slater Roger (International Thomson Business Press, 1994)
This book has twenty three chapters divided into eight study areas. Each chapter focuses on a selection of techniques, illustrated with examples from business, marketing, economics, accounting, finance, and public administration. Preface, A Refresher in Basic Mathematics, Quantitative Information, Data Collection, Presentation of Data, Descriptive Statistics, Measures of Location, Measures of Dispersion, Index of Numbers, Measuring Uncertainty, Probability, Discrete Probability distributions, The Normal Distribution, Statistical Inference, Confidence Intervals, Significance Testing, Non-Parametric Tests, Relating Variables and Predicting Outcomes, Time Series, Correlation, Regression, Multiple Regression and Correlation, Modelling, The Time Value of Money, Linear Programming, Networks, Modelling Stock Control and Queues, Simulation, Mathematical Background, Mathematical Relationships, Matrices, Use of Calculus, Typical Examination Questions, Appendices, Index.